Faktor-Faktor Yang Mempengaruhi Minat Masyarakat Dalam Menggunakan Produk Pembiayaan Pada BMT Indragiri - S, Supriyanto; J, Julina; H, Herlinda (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to identify the factors influencing community interest in using financing products offered by BMT Indragiri. A quantitative method was employed with a survey approach, utilizing questionnaires distributed to potential community members as BMT Indragiri clients. The variables examined include product knowledge, trust in security, ease of access, perception of product benefits, financing costs, and social support. Data were analyzed using regression techniques to identify significant factors influencing community interest. The analysis results show that product knowledge, trust in security, and ease of access are the main factors positively influencing community interest. These findings provide important insights for BMT Indragiri in designing marketing strategies and improving services to increase community participation in using their financing products.